Economic and strategic feasibilities of the use and development of enterprises of civil aviation - Жук, Л. А.; Гелич, Ю. О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
From which depends a providing services in transportation of loads, passengers, mail and luggage by the airtransport of Ukraine, also in the article are determined economic activity of implementation of works orproviding services of cost character of, which have price definiteness.